TRANSAKSI ELEKTRONIK (E-COMMERCE) DALAM PERSPEKTIF FIKIH - Imam Mustofa (Jurnal Hukum Islam, 2012)
This article aims to trace the legal validity of electronic transactions or commonly known as e-commerce, that is conducted using electronic methods such as electronic data interchange and automated data-collection system. E-commerce is preferred because many people presume as having many benefits i.e. demonstrating the value employers professionalism, making efficiency and effectiveness of business services, minimizing capital investment, etcetera. The urgency of this study due to the principles of contract law that are procedurally ignored in the online transaction. E-commerce is assessed valid if the pillars and prevailing conditions in the sale are fulfilled. The study on the validity of e-commerce in this article is not just approached by usul fiqh, but also from the perspective of mu'amalah jurisprudence and fiqhiyyah principles.